The best method for isolated total RNA from durian tissues - Ky, Huynh; Yeap, Swee Keong; Napis, Suhaimi (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2012)
Plant tissues, especially durian tissues contain high content of polysaccharides, polyphenols and other secondary metabolites which can co-precipitate with RNA causing problem in further transcriptomic study. In this experiment, three basic chaotic agents, CTAB, SDS and guanidine are used in three basic protocols for RNA isolation. The effectiveness of each method was determined by spectrophotometer, denaturing agarose gels analysis and northern blot hybridization. CTAB combining with additional sodium acetate precipitation step showed highest yield and best quality of isolated RNA which was free from contaminations of polysaccharides, polyphenols and other secondary metabolites. Furthermore, the total RNA from 4-month old durian flesh of clone D24 was successfully used to construct a cDNA library. In conclusion, CTAB method is effective to isolate total RNA on various types of durian tissues for further gene expression analysis.